Therapeutic potential of human minor salivary gland epithelial progenitor cells in liver regeneration. Issue 1 (December 2017) - Zhang, Chen; Li, Yan; Zhang, Xiang-yu; Liu, Lei; Tong, Hai-zhou; Han, Ting-lu; Li, Wan-di; Jin, Xiao-lei; Yin, Ning-bei; Song, Tao; Li, Hai-dong; Zhi, Juan; et al.
Abstract Liver disease is a serious problem affecting millions of people with continually increasing prevalence. Stem cell therapy has become a promising treatment for liver dysfunction. We previously reported on human minor salivary gland mesenchymal stem cells (hMSGMSCs), which are highly self-renewable with multi-potent differentiation capability. In this study, keratinocyte-like cells with self-regeneration and hepatic differentiation potential were isolated and characterized, and named human minor salivary gland epithelial progenitor cells (hMSG-EpiPCs). hMSG-EpiPCs were easily obtainedvia minor intraoral incision; they expressed epithelial progenitor/stem cell and other tissue stem cell markers such as CD29, CD49f, cytokeratins, ABCG2, PLET-1, salivary epithelial cell markers CD44 and CD166, and the Wnt target related gene LGR5 and LGR6. The cells were induced into functional hepatocytesin vitro which expressed liver-associated markers ALB, CYP3A4, AAT, and CK18. Upon transplantationin vivo, they ameliorated severe acute liver damage in SCID mice caused by carbon tetrachloride (CCl4 ) injection. In a two-thirds partial hepatectomy mouse model, the transplanted cells survived at least 4 weeks and exhibited hepatic potential. These findings demonstrate that hMSG-EpiPCs have potential as a cellular therapy basis for hepatic diseases, physiological and toxicology studies and regenerative medicine.